Low-carbon environment-friendly chloroprene rubber composition and preparation method thereof

By using silane compounds and white carbon black to replace zinc oxide and carbon black additives in the neoprene vulcanization system, low-carbon and environmentally friendly vulcanized rubber is formed, which solves the problems of high carbon emissions and heavy metal pollution in the traditional system and achieves high resistance Combination of thermal properties and excellent mechanical properties.

CN119192698APending Publication Date: 2024-12-27EAST CHINA UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411301368.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-18
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Traditional neoprene vulcanization systems have problems with high carbon emissions, heavy metal pollution and environmental pollution. In particular, zinc oxide and carbon black additives are harmful to the environment and health, and it is difficult to take into account performance and low-carbon environmental protection requirements.

Method used

Using silane compounds as the main vulcanizing agent and white carbon black as the reinforcement agent, combined with an appropriate amount of vulcanization accelerator and acid absorbent, a low-carbon and environmentally friendly neoprene vulcanization system is formed to replace the traditional zinc oxide and carbon black system. , simplify composition and reduce costs.

Benefits of technology

The obtained vulcanized rubber has low toxicity, low pollution, high heat resistance and excellent mechanical properties. The tensile strength and elongation of break are comparable to those of traditional systems. At the same time, it significantly reduces the use of carbon and heavy metals, and meets low carbon. Environmental protection requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention provides a low-carbon environment-friendly chloroprene rubber composition which is prepared from the following raw materials in parts by weight: 100 parts of chloroprene rubber, 0.5-5 parts of a vulcanizing agent, 1-30 parts of a reinforcing agent, 0.5-3 parts of a vulcanization accelerator and 3-5 parts of an acid acceptor, the vulcanizing agent is a silane compound, and the reinforcing agent is white carbon black. The invention provides the method for vulcanizing the chloroprene rubber by using the silane compound as the vulcanizing agent, the vulcanization system has the characteristics of greenness, low carbon, low cost, simple composition and the like, and the prepared rubber material has the advantages of low toxicity, low pollution, high heat resistance and excellent mechanical properties. Compared with a traditional zinc oxide vulcanization system, the invention provides a powerful solution under the condition of reducing the use demand of heavy metals.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of rubber, and in particular to a low-carbon and environmentally friendly chloroprene rubber composition and a preparation method thereof. Background Art

[0002] Chloroprene Rubber (or Neoprene, referred to as CR) is a synthetic rubber made by polymerization with 2-chloro-1,3-butadiene as the main monomer. Chloroprene is one of the earliest synthetic rubbers to achieve industrial production. It is widely used in conveyor belts, wires and cables, and seals due to its flame retardancy, heat resistance, oil resistance, chemical corrosion resistance, ozone cracking resistance, and thermal oxygen aging resistance.

[0003] In the chloroprene rubber vulcanization system, alkali metal oxides, namely zinc oxide (ZnO) system, are usually added for vulcanization, wherein zinc oxide (ZnO) is the main vulcanizing agent, and carbon black (CB) is used as a reinforcing agent, and sulfur (S) is used as a secondary vulcanizing agent. Non-sulfur-adjusted chloroprene rubber also needs to be combined with a vulcanization accelerator 1,2-ethylene thiourea (ETU) to improve the reaction degree of the rubber compound. The vulcanized rubber obtained by this vulcanization system has good physical and mechanical properties, but this vulcanization system has the disadvantages of high carbon emissions, high environmental pollution and heavy metal pollution. For example, ZnO is highly toxic to aquatic organisms, and the EU has listed it as a substance of high concern and gradually restricted its use. ETU is carcinogenic, and harmful gases such as nitrosamines are produced during its production process, which is detrimental to the health of workers and users. The US Environmental Protection Agency has listed it as a Class B2 carcinogen. In this sense, abandoning the traditional zinc oxide vulcanization system and finding a new and more environmentally friendly vulcanization system is of great significance to the development of the chloroprene rubber industry.

[0004] As a major carbon emitter, the rubber industry has been committed to the development of green rubber materials in recent years. In the current production and use of chloroprene rubber products, the commonly used ZnO / S / CB addition system has disadvantages such as higher carbon emissions and heavier environmental pollution. Therefore, it is very necessary to find a vulcanization system that can not only meet the performance requirements of chloroprene rubber vulcanizate, but also reduce the amount of carbon, sulfur and zinc substances used in chloroprene rubber products.

[0005] CN114249933 A uses lead oxide, zinc oxide, and sulfur as vulcanizing agents, and carbon black and white carbon black as reinforcing agents to prepare chloroprene rubber. The chloroprene rubber prepared has a low vulcanization temperature, good weather resistance, good chemical corrosion resistance, good electrical insulation, excellent mechanical strength, and good packaging interface adhesion. However, the vulcanized rubber prepared by this method uses a large amount of heavy metal and high carbon content additives, which is obviously insufficient in terms of low carbon and environmental protection.

[0006] CN114015132A uses zinc oxide as a vulcanizing agent, uses a large amount of white carbon black as a reinforcing agent, and adds a small amount of silane compounds as auxiliary agents to improve the flex resistance, ozone aging resistance and heat resistance of chloroprene rubber. However, the preparation method still uses zinc oxide containing heavy metals as a vulcanizing agent, and adds high-carbon content auxiliary agents such as carbon black, which does not meet the green and low-carbon requirements, and the preparation method is also relatively complicated.

[0007] The above inventions have contributed to improving the various properties of chloroprene rubber, and have also attempted to use low-carbon and environmentally friendly additives. These inventions break the constraints of ZnO-based vulcanizing agents and CB-based reinforcing agents, but have the characteristics of being unable to take into account both performance and low-carbon and environmentally friendly performance. Summary of the invention

[0008] The invention aims to provide a low-carbon and environmentally friendly chloroprene rubber composition and a preparation method thereof. Compared with a traditional chloroprene rubber auxiliary agent system, the composition does not use zinc oxide in a vulcanization system and does not use carbon black in a reinforcement system. The composition has the characteristics of low carbon and environmental protection, simple composition, low cost, etc. The tensile strength and elongation at break of the prepared vulcanized rubber are equivalent to those of a traditional vulcanization system, and the composition has outstanding advantages such as lower toxicity and pollution, higher heat resistance, etc.

[0009] In order to achieve the above objectives, the specific plan is as follows:

[0010] A low-carbon and environmentally friendly chloroprene rubber composition comprises the following parts by weight: 100 parts of chloroprene rubber, 0.5 to 5 parts of a vulcanizing agent, 1 to 30 parts of a reinforcing agent, 0.5 to 3 parts of a vulcanization accelerator, and 3 to 5 parts of an acid absorber, wherein the vulcanizing agent is a silane compound and the reinforcing agent is white carbon black.

[0011] The silane compounds mentioned above refer to a class of organic silicon compounds containing silaneoxy functional groups, and the end groups contain one or more of alkyl, alkenyl, mercapto, amino, epoxy, and acryloxy groups, which act as the main vulcanizing agent. The rubber after vulcanization generally has the characteristics of green and low carbon, low toxicity, low pollution, and high heat resistance. The silane compound includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane (KH580), γ-mercaptopropyltriethoxysilane (KH590), bis-(3-triethoxysilylpropyl)tetrasulfide (Si69), γ-aminopropyltrimethoxysilane (KH540), γ-aminopropyltriethoxysilane (KH550), γ-aminoethylaminopropyltrimethoxysilane (KH792), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), γ-(2,3-epoxypropoxy)propyltriethoxysilane (KH561), and γ-methacryloxypropyltrimethoxysilane (KH570), and their molecular structural formulas are shown in Table 1 below.

[0012] Table 1

[0013]

[0014]

[0015] Preferably, the terminal groups of the silane compounds in the present invention contain one or more of alkyl, alkenyl, mercapto, amino, epoxy, and acryloxy groups.

[0016] Preferably, the silane compound of the present invention includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane (KH580), γ-mercaptopropyltriethoxysilane (KH590), bis-(3-triethoxysilylpropyl)tetrasulfide (Si69), γ-aminopropyltrimethoxysilane (KH540), γ-aminopropyltriethoxysilane (KH550), γ-aminoethylaminopropyltrimethoxysilane (KH792), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), γ-(2,3-epoxypropoxy)propyltriethoxysilane (KH561), and γ-methacryloxypropyltrimethoxysilane (KH570).

[0017] As a preference, among the vulcanizing agents, when only one silane compound is used alone, γ-aminopropyltriethoxysilane (KH550) has the best comprehensive performance. This is because compared with other silane compounds, the rubber compound prepared by the vulcanization system in which it is used as a vulcanizing agent has higher tensile strength, higher degree of vulcanization, and better heat resistance.

[0018] And based on 100 parts by weight of chloroprene rubber, the amount of γ-aminopropyltriethoxysilane (KH550) is preferably 1 to 3 parts by weight. Excessive use of vulcanizing agent will cause premature vulcanization and over-vulcanization of chloroprene rubber during processing, reducing the tensile strength of chloroprene rubber vulcanizate; too little use of vulcanizing agent will result in low vulcanization speed of chloroprene rubber and insufficient vulcanization degree. The appropriate amount of vulcanizing agent can ensure rapid vulcanization and achieve the optimal vulcanization degree.

[0019] The reinforcing agent includes one or more of fumed silica and precipitated silica. The silica component is silicon dioxide. As a green, non-toxic, odorless and excellent additive, it is very suitable for replacing traditional carbon black as a reinforcing agent in the rubber industry. Fumed silica has a finer particle size, a larger specific surface area, and a better reinforcing effect, but the processing performance is worse. The mechanical strength of rubber reinforced with precipitated silica is slightly lower, the dielectric properties are poor, but the heat aging resistance is better, and the mixed rubber processing performance is better.

[0020] Preferably, the reinforcing agent of the present invention uses fumed silica and precipitated silica together, so that the chloroprene rubber compound has not only good mechanical properties but also good processing properties.

[0021] The vulcanization accelerator includes one or more of dibutyltin dilaurate, stearic acid, zinc stearate, zinc chloride, and zinc methacrylate. Dibutyltin dilaurate has the function of promoting the grafting of silane compounds to organic matter and promoting the condensation between compounds, and has the universality for silane compounds. Stearic acid, zinc stearate, zinc chloride, and zinc methacrylate have the function of activating chloroprene rubber molecular chains to participate in the vulcanization reaction.

[0022] Preferably, based on 100 parts by weight of chloroprene rubber, the vulcanization accelerator of the present invention is 0.5 to 3 parts by weight of dibutyltin dilaurate and 1 to 5 parts by weight of zinc stearate; more preferably, the vulcanization accelerator of the present invention is 1 part by weight of dibutyltin dilaurate and 3.5 parts by weight of zinc stearate. Compared with other vulcanization accelerator combinations, this accelerator combination enables the rubber compound to have a more suitable vulcanization degree and a faster vulcanization rate.

[0023] The acid absorber of the present invention mainly functions to absorb hydrogen chloride generated by dechlorination during the vulcanization of chloroprene rubber. The acid absorber comprises one or more of metal oxides, metal hydroxides and composite metal hydroxides, wherein the metal oxides comprise one or more of magnesium oxide and calcium oxide, the metal hydroxides comprise one or more of magnesium hydroxide and calcium hydroxide, and the composite metal hydroxide comprises hydrotalcite.

[0024] Furthermore, the acid absorber of the present invention is preferably magnesium oxide. Compared with other acid absorbers, magnesium oxide has higher acid absorption efficiency and more stable effect as an acid absorber. Based on 100 parts by weight of chloroprene rubber, the amount of magnesium oxide is 3 to 5 parts by weight. If the amount of magnesium oxide is too little, the sulfurization scorch is aggravated; if the amount of magnesium oxide is too much, the degree of vulcanization of the rubber is insufficient.

[0025] The chloroprene rubber composition of the present invention can be prepared by a general method. Preferably, its preparation method comprises the following steps:

[0026] Step 1: Plasticate the raw chloroprene rubber, the plasticate conditions are: temperature 50℃~70℃, rotor speed 50r / min~70r / min, time 2~4min;

[0027] Step 2: Add a reinforcing agent, an accelerator, an acid absorber and a vulcanizing agent to the plasticized rubber prepared in step 1 in sequence and mix them to prepare a mixed rubber. The mixing conditions are: temperature 50° C. to 70° C., rotor speed 50 r / min to 70 r / min, and time 5 to 7 min;

[0028] Step 3: placing the mixed rubber material prepared in step 2 in a vulcanizer for vulcanization to obtain vulcanized rubber, and the vulcanization conditions are: temperature 150° C. to 170° C., pressure 8 to 12 MPa, and time 8 to 40 min.

[0029] Step 4: placing the vulcanized rubber prepared in step 3 in hot water for water bath heating to obtain a finished product. The heating conditions are: temperature 60° C. to 120° C., time 0.5 to 15 h.

[0030] The products made of the chloroprene rubber composition of the present invention can also be used in transmission belts, conveyor belts, hoses and sealing elements.

[0031] The effects and advantages of the present invention are as follows: providing a set of chloroprene rubber auxiliary agent systems that replace traditional high-carbon content, high-heavy metal content, and high-pollution chloroprene rubber, providing a method for vulcanizing chloroprene rubber using silane compounds as vulcanizing agents, the vulcanization system has the characteristics of being green and low-carbon, low-cost, and simple in composition, the prepared rubber material has low carbon content, high heat resistance, low toxicity, and low pollution, and the vulcanized rubber has excellent mechanical properties. DETAILED DESCRIPTION

[0032] The following is a further description in combination with specific implementation cases and comparative cases. The implementation cases do not limit the present invention in any form, and all technologies realized based on the above content of the present invention belong to the protection scope of the present invention.

[0033] The raw materials used in the embodiments and comparative examples are as follows:

[0034] Mercaptan-regulated chloroprene rubber, CR2322, was purchased from Changzhi Huojia Industrial Co., Ltd.;

[0035] γ-Aminopropyltriethoxysilane, KH550, was purchased from Nanjing Dulai Biotechnology Co., Ltd.;

[0036] γ-Aminoethylaminopropyltrimethoxysilane, KH792, was purchased from Shanghai Myril Biochemical Technology Co., Ltd.;

[0037] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane, KH560, was purchased from Nanjing Dulai Biotechnology Co., Ltd.;

[0038] γ-Mercaptopropyltriethoxysilane, KH590, was purchased from Nanjing Dulai Biotechnology Co., Ltd.;

[0039] Bis-(3-triethoxysilylpropyl)tetrasulfide, Si-69, was purchased from Sinopharm Chemical Reagent Co., Ltd.;

[0040] White carbon black, SiO2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0041] Dibutyltin dilaurate, DY-12, was purchased from Shanghai Myril Biochemical Technology Co., Ltd.;

[0042] Zinc stearate, ZnSt, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0043] Zinc chloride, ZnCl2, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.

[0044] Magnesium oxide, MgO, was purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;

[0045] Hydrotalcite, LDHs, was purchased from Shanghai Zhonghe Chemical Technology Co., Ltd.;

[0046] Zinc oxide, ZnO, was purchased from Aladdin Reagent Co., Ltd.;

[0047] Carbon black N330, CB-N330, purchased from Tianjin Huacai Chemical Co., Ltd.;

[0048] 1,2-Ethylenethiourea, ETU, was purchased from Ningbo Aikemu New Materials Co., Ltd.;

[0049] N-Cyclohexyl-2-benzothiazolesulfenamide, CZ, was purchased from Ningbo Aikemu New Materials Co., Ltd.;

[0050] Tetraethylthiuram disulfide, TETD, was purchased from Ningbo Aikemu New Materials Co., Ltd.;

[0051] Stearic acid, HSt, was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.;

[0052] The experimental items and test methods involved in the present invention are as follows:

[0053] Calculation of theoretical organic carbon content (ThOC) and heavy metal content: The total carbon content and heavy metal content in the additive system are calculated based on the chemical composition, relative molecular mass and formulation dosage of each component.

[0054] Heat resistance test method: Dynamic mechanical analyzer (DMA) was used to test the creep of materials at different temperatures according to GB-T 42279-2022 standard. Chloroprene vulcanizates with different formulations were made into 30mm×4mm×2mm splines. In the tensile mode, a stress of 0.15MPa was applied. The test lasted for 60min, and the creep of the samples at 80℃, 120℃, and 160℃ were measured.

[0055] Test method for vulcanization performance: Use a rotorless vulcanizer, according to GB / T 16584-1996 standard, test at 160℃ for 30min, with a swing angle of 0.5 degrees, to obtain the vulcanization curve of torque and time during the isothermal vulcanization of the rubber compound. This curve can be used to obtain the positive vulcanization time T of the rubber compound. 90 (min), maximum torque M H (dN.m) and other vulcanization characteristic parameters.

[0056] Mechanical properties test method: Use a universal tensile testing machine to test the tensile strength (MPa), elongation at break (%) and 300% tensile stress (MPa) of the vulcanized rubber according to GB / T 528-2009 standard, and the tensile rate is 500mm / min. Use a Shore durometer to measure the Shore A hardness of the vulcanized rubber at room temperature according to GB / T 23651-2009 standard.

[0057] Examples 1-15, Comparative Examples 1-7.

[0058] The embodiments of the present invention and the comparative examples are prepared according to the formulas in Table 2 and Table 3: 50g of chloroprene rubber raw rubber is mixed in an internal mixer, and plasticized for 3min at a temperature of 60°C and a rotor speed of 60r / min. Then, vulcanizing agent, reinforcing agent, accelerator and acid absorbent are added according to the formula ratio, and the material is unloaded after mixing for 6min. The chloroprene rubber mixed rubber after blending is thinly passed 3 to 5 times at room temperature in an open mixer and rolled flat. 4 to 6g of the mixed rubber is taken for testing the vulcanization performance, and the other parts are used for testing the heat resistance and mechanical properties after vulcanization on a flat vulcanizing press.

[0059] Add the cut-to-size mixed rubber sheet into the vulcanizing mold, place the mold in the vulcanizing machine, set the vulcanization conditions of temperature 160℃ and pressure 12MPa to press vulcanize, and the vulcanization time is the measured positive vulcanization time T of the rubber compound. 90Finally, dumbbell-shaped specimens were made using a dumbbell-shaped sample making machine for heat resistance and mechanical properties tests.

[0060]

[0061]

[0062]

[0063] The performance test results of the embodiments of the present invention and the comparative examples are shown in Table 4 and Table 5.

[0064] Example 1 uses γ-aminopropyltriethoxysilane (KH550) as a vulcanizing agent, white carbon black as a reinforcing agent, dibutyltin dilaurate and zinc stearate as vulcanization accelerators, and magnesium oxide as an acid absorber. The dosage of each component in the formula is within the optimal range. Example 1 has the best comprehensive performance. Excluding the rubber main body, the theoretical organic carbon content of all added additives is 8.39%, and the theoretical heavy metal content is 2.06%. The combined content of the two is at a very low level in all examples, and the low-carbon and environmentally friendly nature of this formula is very prominent. The creep of Example 1 at a high temperature of 160°C for 1h is only 11.55%, and the heat resistance at high temperature is very outstanding. At the same time, its vulcanization and mechanical properties are also very outstanding, and its positive vulcanization time T 90 It is relatively short, at 20.19min; the tensile strength is the largest, at 18.96MPa; the 300% elongation stress can reach 3.77MPa; and the hardness can reach 57HA.

[0065] Compared with Example 1, in Examples 2 to 5, the vulcanizing agent γ-aminopropyltriethoxysilane (KH550) is replaced by polyamino, epoxy, mercapto, and polysulfide silane compounds, and their vulcanization efficiency and tensile strength are not as good as those in Example 1.

[0066] Compared with Example 1, the amount of the vulcanizing agent γ-aminopropyltriethoxysilane (KH550) in Examples 6 and 7 is reduced to 1 part and increased to 5 parts, respectively. The vulcanization efficiency and tensile strength are not as good as those in Example 1.

[0067] Compared with Example 1, Example 8 uses a smaller amount of reinforcing agent white carbon black, and its vulcanization efficiency and tensile strength are not as good as those of Example 1.

[0068] Compared with Example 1, the amount of dibutyltin dilaurate used in Examples 9 and 10 was reduced to 0 parts and increased to 3 parts respectively, but the tensile strength was not as good as that in Example 1.

[0069] Compared with Example 1, the vulcanization accelerator zinc stearate is replaced by zinc chloride in Example 11, and its tensile strength is not as good as that in Example 1.

[0070] Compared with Example 1, the amount of accelerator zinc stearate in Examples 12 and 13 is reduced to 0 parts and 2.5 parts, and the vulcanization efficiency and tensile strength thereof are not as good as those in Example 1.

[0071] Compared with Example 1, the amount of magnesium oxide used as the acid absorber in Example 14 is reduced to 0, and its tensile strength is not as good as that in Example 1.

[0072] Compared with Example 1, the acid absorber magnesium oxide in Example 15 is replaced by hydrotalcite, and its tensile strength is not as good as that in Example 1.

[0073] Compared with Comparative Examples 1 and 3, Comparative Example 2 uses a ZnO vulcanization system in the formula, and the amount of accelerator 1,2-ethylene thiourea (ETU) is 0 parts in Comparative Example 1, 0.5 parts in Comparative Example 2, and 1 part in Comparative Example 3, respectively. N-cyclohexyl-2-benzothiazole sulfonamide (CZ) and tetraethylthiuram disulfide (TETD) are used as accelerators, stearic acid is used as a plasticizer, magnesium oxide is used as an acid absorber, and no reinforcing agent is used. The amount of ETU in Comparative Example 2 is moderate, the tensile strength is the highest, the vulcanization time is short, and the overall performance is the best. The addition of ETU can improve the vulcanization efficiency of CR. Comparative Example 1 does not add ETU, and the vulcanization efficiency is not as good as that of Comparative Example 2. Comparative Example 3 adds excessive ETU, and the tensile strength is not as good as that of Comparative Example 2.

[0074] Compared with Example 8, Comparative Example 4 uses a ZnO vulcanization system instead of a silane compound vulcanization system in the formula, uses ETU as an accelerator and uses a preferred system of CZ and TETD, and uses 5 parts of carbon black as a reinforcing agent instead of 5 parts of white carbon black. Under the premise of the same amount of reinforcing agent, the tensile strength of Comparative Example 4 is equivalent to that of Example 8, but the carbon content and heavy metal content in the auxiliary agent are much higher than those in Example 8, and the low-carbon environmental protection is poor, and the heat resistance at high temperature is poor.

[0075] Compared with Example 1, in Comparative Example 5, a ZnO vulcanization system is used in the formula instead of a silane compound vulcanization system, an accelerator is ETU and a preferred system of CZ and TETD is used, and a reinforcing agent is 15 parts of carbon black instead of 15 parts of white carbon black. Under the premise that the reinforcing agent is used in the same amount, the tensile strength of Comparative Example 5 is equivalent to that of Example 1, but the carbon content and heavy metal content in the auxiliary agent are much higher than those in Example 1, and the low-carbon environmental protection and heat resistance are poor.

[0076] Compared with Example 1, in Comparative Example 6, the amount of KH550 in the formula is increased to 10 parts, and the formulas of other components are the same. Its tensile strength is greatly reduced, the elongation at break is reduced, and the hardness is increased. This result is due to the excessive amount of vulcanizing agent, which leads to excessive crosslinking and poor performance.

[0077] Comparative Example 7 is compared with Comparative Example 2. Comparative Example 7 uses a silane compound vulcanization system, while Comparative Example 2 uses a ZnO vulcanization system, and neither of them uses a reinforcing agent. The system of Comparative Example 2 has a higher content of heavy metals, and its green environmental protection is far worse than that of Comparative Example 7. Its heat resistance at high temperature is worse than that of Comparative Example 7. At the same time, the tensile strength of the two systems is equivalent without adding a reinforcing agent.

[0078] Compared with Example 1, Comparative Example 7 does not add reinforcing agent white carbon black, while Example 1 adds 15 parts of reinforcing agent white carbon black, and other components are the same. The vulcanization efficiency and tensile strength of Comparative Example 7 are not as good as those of Example 1.

[0079] The above-mentioned embodiments are for the convenience of the staff in the technical field to better understand and use the present invention, and do not fully demonstrate the implementation method of the present invention. Therefore, the present invention is not limited to the above embodiments, and the improvements and modifications made according to the description of the present invention are within the scope of the claims of the present invention.

Claims

1. A chloroprene rubber composition, characterized in that The invention comprises the following parts by weight: 100 parts of chloroprene rubber, 0.5 to 5 parts of a vulcanizing agent, 1 to 30 parts of a reinforcing agent, 0.5 to 3 parts of a vulcanization accelerator, and 3 to 5 parts of an acid absorbent, wherein the vulcanizing agent is a silane compound and the reinforcing agent is white carbon black.

2. A chloroprene rubber composition according to claim 1, characterized in that: The silane compound contains a silaneoxy functional group, and the terminal group contains one or more of an alkenyl group, a mercapto group, an amino group, an epoxy group, and an acryloxy group.

3. A chloroprene rubber composition according to claim 2, characterized in that: The silane compound includes one or more of vinyltrimethoxysilane, vinyltriethoxysilane, vinyltriacetoxysilane, γ-mercaptopropyltrimethoxysilane (KH580), γ-mercaptopropyltriethoxysilane (KH590), bis-(3-triethoxysilylpropyl)tetrasulfide (Si69), γ-aminopropyltrimethoxysilane (KH540), γ-aminopropyltriethoxysilane (KH550), γ-aminoethylaminopropyltrimethoxysilane (KH792), γ-(2,3-epoxypropoxy)propyltrimethoxysilane (KH560), γ-(2,3-epoxypropoxy)propyltriethoxysilane (KH561), and γ-methacryloxypropyltrimethoxysilane (KH570).

4. A chloroprene rubber composition according to claim 1, characterized in that: The white carbon black is one or more of gas phase white carbon black and precipitated white carbon black.

5. A chloroprene rubber composition according to claim 1, characterized in that: The vulcanization accelerator is one or more of dibutyltin dilaurate, stearic acid, zinc stearate, zinc chloride, and zinc methacrylate. Preferably, based on 100 parts by weight of chloroprene rubber, the vulcanization accelerator of the present invention is 0.5 to 3 parts by weight of dibutyltin dilaurate and 1 to 5 parts by weight of zinc stearate; more preferably, the vulcanization accelerator of the present invention is 1 part by weight of dibutyltin dilaurate and 3.5 parts by weight of zinc stearate.

6. A chloroprene rubber composition according to claim 1, characterized in that: The acid absorbent includes one or more of metal oxides, metal hydroxides, and composite metal hydroxides. The metal oxides include one or more of magnesium oxide and calcium oxide. The metal hydroxides include one or more of magnesium hydroxide and calcium hydroxide. The composite metal hydroxide includes hydrotalcite.

7. The method for preparing a chloroprene rubber composition according to claim 1, characterized in that: The following steps are involved: Step 1: Plasticate the raw chloroprene rubber, the plasticate conditions are: temperature 50℃~70℃, rotor speed 50r / min~70r / min, time 2~4min; Step 2: Add a reinforcing agent, an accelerator, an acid absorber and a vulcanizing agent to the plasticized rubber prepared in step 1 in sequence, and mix them to prepare a mixed rubber. The mixing conditions are: temperature 50° C. to 70° C., rotor speed 50 r / min to 70 r / min, and time 5 to 7 min; Step 3: placing the mixed rubber material prepared in step 2 in a vulcanizer for vulcanization to obtain vulcanized rubber, and the vulcanization conditions are: temperature 150° C. to 170° C., pressure 8 to 12 MPa, and time 8 to 40 min. Step 4: placing the vulcanized rubber prepared in step 3 in hot water for water bath heating to obtain a finished product. The heating conditions are: temperature 60° C. to 120° C., time 0.5 to 15 h.

8. Use of the chloroprene rubber composition according to any one of claims 1 to 7 in transmission belts, conveyor belts, hoses and seals.